Multiphasic scaffold for scapholunate interosseous ligament reconstruction: A study in the rabbit knee. Issue 8 (7th July 2020) - Lui, Hayman; Vaquette, Cedryck; Denbeigh, Janet M.; Bindra, Randy; Kakar, Sanjeev; van Wijnen, Andre J.
Abstract: Scapholunate interosseous ligament tears are a common wrist injury in young and active patients that can lead to suboptimal outcomes after repair. This research aims to assess a multiphasic scaffold using 3D‐printing for reconstruction of the dorsal scapholunate interosseous ligament. The scaffold was surgically implanted in vivo in the position of the native rabbit medial collateral ligament. Two branches of treatment were implemented in the study. In the first group, the rabbits (n = 8) had the knee joint fixed in flexion for 4 weeks using 1.4 mm K‐wires prior to sample harvesting. The second group (n = 8) had the rabbit knee joint immobilized for 4 weeks prior to K‐wire removal and mobilization for an additional 4 weeks prior to sample harvesting. Overall, samples were harvested at 4 weeks post‐surgery (immobilized group) and eight weeks post‐surgery (mobilized group). Mechanical tensile testing (n = 5/group) and histology (n = 3/group) of the constructs were conducted. Tissue integration and maturation were observed resulting in increased mechanical strength of the operated joint at 8 weeks ( P < .05). Bone and ligament tissues were regenerated in their respective compartments with structural and mechanical properties approaching those reported for the human dorsal SLIL ligament. Clinical Significance: This proof of concept study has demonstrated that the synthetic multiphasic scaffold was capable of regenerating both bone and ligament while also withstanding the physiological load once implanted in the rabbit knee. The artificial scaffold may provide an alternative to current techniques for reconstruction of scapholunate instability or other ligament injuries in the hand and wrist.